Effect of duplex aging on microstructure and mechanical behavior of beta titanium alloy Ti–15V–3Cr–3Al–3Sn under unidirectional and cyclic loading conditions. (April 2015) - Santhosh, R.; Geetha, M.; Saxena, V.K.; Nageswara Rao, M.
Highlights: Duplex aging (DA) in place of single aging (SA) of beta titanium alloy 15-3 led to higher strength. Higher strength after DA was related to finer and denser precipitation of α particles. DA resulted in major improvement in HCF life over SA. Freedom from micro-PFZs and grain boundary α led to better HCF life after DA. Improved HCF life after DA was achieved even at a high mean stress level (stress ratio = +0.3). Abstract: The microstructure and mechanical behavior of beta titanium alloy Ti–15V–3Cr–3Al–3Sn (Ti15-3) under unidirectional and high cycle fatigue (HCF) loading conditions were studied after single aging (SA) and duplex aging (DA). After SA, well-developed grain boundary α and micro precipitate free zones (micro PFZs) were present in the microstructure. Whereas after DA, grain boundary α was poorly developed and micro PFZs were absent. DA resulted in smaller size, higher density and volume fraction of alpha particles. DA led to higher work hardening rate, better strength-ductility combination and higher HCF life. Improved mechanical behavior after DA is explained based on microstructural observations.